Coupled ultimate capacity of CFRP confined concrete-filled steel tube columns under compression-bending-torsion load. (June 2021) - Wang, Yu-Hang; Wang, Yu-Yan; Zhou, Xu-Hong; Deng, Ran; Lan, Yong-Sen; Luo, Wei; Li, Peng; Yang, Qing-Shan; Ke, Ke
Highlights: Comprehensive finite element modelling was established and verified by test data. Full-range behavior was analyzed under compression-bending-torsion load. Parametric study on the ultimate capacity of CFRP-CFST columns was conducted. Capacity correlations and simplified design formulae were proposed and verified. Abstract: Carbon fiber reinforced polymer confined concrete-filled steel tube (CFRP-CFST) columns are having promising utilization in offshore structures, which are usually subjected to the combination of axial forces, bending moments, and torsional moments. This paper thus presents a finite element (FE) study on CFRP-CFST columns under combined compression-bending-torsion load. The comprehensive FE modelling was established and then validated by the experimental data. Analysis of typical failure modes, load-deformation relations and full-range behavior was performed based on the FE simulation. Meanwhile, parametric analysis was conducted to reveal the sensitive parameters as well as their influence on the structural behavior and ultimate capacity of CFRP-CFST columns. Finally, correlation relations which can reasonably characterize the coupled ultimate capacity of columns were obtained and validated. Correspondingly, simplified design formulae for predicting the ultimate capacity correlation of CFRP-CFST columns under compression-bending-torsion load were proposed.